If A = [ a − b b a ] , where a , b are real numbers, then find e A t .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution, Brian. Your time in putting all this together is appreciated. There is a more brute force way of demonstrating the same, but this is better in showing some of the interesting properties of matrix exponentiation.
Log in to reply
Thanks! Yeah, there are a lot of ways to see this same result. The fastest way I know of is just to note the eigenvalues of A t are a t ± b t i , so under a change of basis, e A t just looks like e a t ± b t i = e a t ( cos ( b t ) ± i sin ( b t ) ) . Therefore, the final result can be seen as a real matrix form of complex exponentiation!
Log in to reply
I used that approach, but I kinda doubted its validity. Thanks! :)
Log in to reply
@A Former Brilliant Member – To be a formal solution, you would need to check a few things (that At is diagonalizable, what the basis-change matrix is), but it is a correct intuition in this case.
Log in to reply
@Brian Moehring – Yep, yep. It is a pretty cool method too! :P
Problem Loading...
Note Loading...
Set Loading...
Let's start with some basics:
Therefore, we may write A t = a t [ 1 0 0 1 ] + b t [ 0 − 1 1 0 ] = a t I 2 + b t [ 0 − 1 1 0 ] , and since I 2 commutes with every matrix, we can use the property I mentioned above to split the problem into two simpler parts:
Therefore, we compute exp ( a t I 2 ) = k = 0 ∑ ∞ k ! ( a t ) k I 2 k = k = 0 ∑ ∞ k ! ( a t ) k I 2 = e a t I 2 exp ( b t [ 0 − 1 1 0 ] ) = k = 0 ∑ ∞ k ! ( b t ) k [ 0 − 1 1 0 ] k = k = 0 ∑ ∞ ( 2 k ) ! ( b t ) 2 k [ 0 − 1 1 0 ] 2 k + k = 0 ∑ ∞ ( 2 k + 1 ) ! ( b t ) 2 k + 1 [ 0 − 1 1 0 ] 2 k + 1
To simplify this latter expression, note that [ 0 − 1 1 0 ] 2 k = ( − I 2 ) k = ( − 1 ) k I 2 , [ 0 − 1 1 0 ] 2 k + 1 = ( − 1 ) k [ 0 − 1 1 0 ] so that it becomes exp ( b t [ 0 − 1 1 0 ] ) = k = 0 ∑ ∞ ( 2 k ) ! ( b t ) 2 k ( − 1 ) k I 2 + k = 0 ∑ ∞ ( 2 k + 1 ) ! ( b t ) 2 k + 1 ( − 1 ) k [ 0 − 1 1 0 ] = cos ( b t ) I 2 + sin ( b t ) [ 0 − 1 1 0 ] = [ cos ( b t ) − sin ( b t ) sin ( b t ) cos ( b t ) ]
Finally, putting it all together, we have e A t = e a t I 2 [ cos ( b t ) − sin ( b t ) sin ( b t ) cos ( b t ) ] = e a t [ cos ( b t ) − sin ( b t ) sin ( b t ) cos ( b t ) ] .